The effect of Home Visit on the learning outcomes of class 3 students in SD IQ Al-Islam - Lukinah, Ina (ETUDE: Journal of Educational Research, 2021)
Background: Home environment as the first place of education for students should be able to provide a good role for its development. In fact, it is realized that there are still many problematic families or home environments that cause problems for students, especially in the learning process at school. Students' problems can be seen from where the problems come from, both from relationships in the family and family situations. Family problems and family situations can affect students in school in terms of learning concentration and school activities, resulting in decreased student achievement. Therefore, guidance and counseling teachers need to carry out home visits. Purpose: The purpose of this study was to analyze the effect of implementing a home visit on student learning outcomes. Design and methods: This study uses quantitative research where data collection in the field is carried out by means of a questionnaire (Questionnaire). The object of this research is the home visit service and the learning outcomes of grade 3 students at SD IQ Al-Islam. The location in this study was conducted at SD IQ Al-Islam and the time of the study was conducted in November 2020. Results: The results of this study indicate that the implementation of a home visit has a positive effect on student learning outcomes by 96% in grade 3 SD IQ Al-Islam, meaning the better the implementation of the home visit will improve student learning outcomes.